2016
DOI: 10.1002/cam4.647
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hemoglobin levels and their interactions with cigarette smoking on survival in nasopharyngeal carcinoma patients

Abstract: There is very little published information regarding the prognostic value of hemoglobin (Hb) levels combined with smoking on the survival of patients with nasopharyngeal carcinoma (NPC), and the interactions between them remain unclear. A total of 2440 NPC patients were confirmed, and multivariate analysis was performed to identify valuable prognostic Hb levels in the entire population and in the cohort of smokers. The survival differences were compared using log‐rank tests. The multiplicative and additive int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…anemia is either present at the pre-treatment period or emerges de novo during the treatment course) and searched for a particular cut-off Hgb value that may be useful in the further prognostic stratification of such patients. [14][15][16][17][18][19][20][21] However, forming the basis for the present research, the reported results conflicted with the proposed Hgb cut-offs and the true influence of anemia on patients' outcomes, which may have been affected by the significant variations in anemia definitions. [14][15][16][17][18][19][20][21] Our data showed that pre-C-CRT anemia adversely affected the OS (P=0.007), LRPFS (P=0.021), and PFS (P=0.003) outcomes of NPC patients.…”
Section: Discussioncontrasting
confidence: 59%
“…anemia is either present at the pre-treatment period or emerges de novo during the treatment course) and searched for a particular cut-off Hgb value that may be useful in the further prognostic stratification of such patients. [14][15][16][17][18][19][20][21] However, forming the basis for the present research, the reported results conflicted with the proposed Hgb cut-offs and the true influence of anemia on patients' outcomes, which may have been affected by the significant variations in anemia definitions. [14][15][16][17][18][19][20][21] Our data showed that pre-C-CRT anemia adversely affected the OS (P=0.007), LRPFS (P=0.021), and PFS (P=0.003) outcomes of NPC patients.…”
Section: Discussioncontrasting
confidence: 59%
“…As a potential biological mechanism, it has been suggested that smoking may stimulate erythropoiesis in a dose-related manner due to hypoxia, which is induced by smoking. In addition, hypoxia is likely to suppress hepcidin expression [8919202122]. …”
Section: Discussionmentioning
confidence: 99%
“…In some studies, post-treatment Hb level was considered to be of predictive value, but the value of pre-treatment Hb level needs to be further confirmed. 37 , 38 In addition, malignant tumors, infections and other factors can also activate the immune and inflammatory system and affect the levels of Hb, NLR and PLR and other parameters. 39 , 40 …”
Section: Discussionmentioning
confidence: 99%